Fenologi, Morfologi, dan Hasil Empat Aksesi Kacang Bambara (Vigna subterranea (L.) Verdc.) - Manggung, Raden Enen Rindi; Qadir, Abdul; Ilyas, dan Satriyas (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2016)
ABSTRACTCharacterization and evaluation of genetic potential of bambara groundnut accessions is very important in order to obtain accessions with high yield potential and early maturity. The objective of this research was to study the phenology, morphology, and yield of four bambara groundnut accessions. This experiment was conducted using a randomized completely block design with one factor i.e. origin of accessions (Bogor and Sukabumi black testa, Sumedang black and brown testa). The results showed that days to seedling emergence of Sumedang brown testa were 9.7 days after sowing (DAS), three other accessions ranged from 8.0 to 8.3 DAS. Days to 75% flowering of Sumedang brown testa was 45.3 days, the other three accessions ranged from 46.0 to 46.7 DAS. Days to pod formation of Bogor and Sumedang accessions with black testa were 49 DAS, Sumedang brown testa at 50 DAS, and Sukabumi accession at 54 DAS. Physiological seed maturity of Bogor and Sukabumi accessions at 112 DAS, Sumedang brown testa at 116 DAS and black testa at 128 DAS. Morphological variation of four bambara groundnut accessions included color of plumule, petiole, seed coat (testa), and leaf shape. Accessions of Sukabumi and Bogor black testa were potential to be developed further because of its showing higher number and weight of pods, and earlier maturity compared to those of Sumedang accessions with black and brown testa.Keywords: early maturity, leaf shape, pod, seedling emergence, testa color